Weeb Student Self-Concept Due to Action Anime (Case Study of Weeb Student of Syekh-Yusuf Islamic University Tangerang) - Eroh Khumaeroh; Helena Mufti Sartika; Ilham Herda Fauzi; Wisnu Maulana Malik Ibrahim (JOURNAL SAINS STUDENT RESEARCH, 2023)
Developments in technology and information make it easier for people to access the internet, such as watching movies or dramas online through several platforms, one of which is currently popular is anime. This anime phenomenon has penetrated various circles of adults, teenagers, to children. As a result, from watching anime, many people change their self-concept and behavior to be the same as anime characters. This study aims to elaborate on the formation of the self-concept of a weeb or anime lover in everyday life. The research method used is a descriptive qualitative method with a case study approach. Data collection was done by interviews and observations. This research focuses on how individuals or weebs find their identity and concepts in themselves after watching anime films. This research applies Sven Windahl’s theory of uses and effects. The results showed that this self-experience encouraged subjects to learn Japanese and also gave freedom to imagine and interacting with their favorite anime characters.